Role of Sonography in the Assessment of Severity and its’ Correlation with Platelet Count of Dengue Fever in Children - Ferdoucy, Sultana Amena; Parveen, Ruma; Rashid, Mamun ur; Rahaman, Khadiza; Begum, Iffat Ara; Bhuyian, Rokanuzzaman; Moureen, Adneen (Bangladesh Journal of Infectious Diseases, 2024)
Background: Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF), and Dengue Shock Syndrome are among the disorders caused by the Dengue virus. Objective: The purpose of the present study was to assess severity of dengue by ultrasound findings and to correlate the ultrasound findings with blood platelet count. Methodology: This prospective study was conducted in the at Dr. MR Khan Shishu Hospital & ICH, Dhaka, Bangladesh from May 2019 to October 2019. Total 107 dengue children patients aged from 0 to14 years old were selected as a study population. Purposive sampling technique was used. Data were collected with pre-tested, modified and structured questionnaire. Complete blood count/picture (CBC), Laboratory based serological tests and Ultra sonographic test were performed. Results: USG studies were performed on all patients with severe dengue fever. Most of the dengue patients had blood platelet counts under 100000. USG studies revealed that Pericholecystic collection was the most common finding in dengue patients followed by thickening of GB, pleural effusion, pelvic collection, peri renal collection and ascites. In this study there was positive correlation between sonographic findings with platelet count of Dengue fever in children. The Mean and SD of platelet count was 56635.51±26267.633. Paired Samples correlations of sonographic finding with platelet findings were positively correlated but paired difference and t test result was significant. Clinical features and thrombocytopenia are help in lead us to the diagnosis of dengue. There were 86.92% patients had platelet counts under 100,000. There was positive correlation between sonography findings and platelet count. About 95.33% of the patients had Pericholecystic collection and 92.50% had GB Wall edema. Conclusion: in conclusion, USG abdomen showing Pericholeystic collection and GB wall edema is a useful marker for early diagnosis of severe Dengue Fever. Bangladesh Journal of Infectious Diseases, June 2024;11(1):16-21